Blended foods for tube-fed children: a safe and realistic option? A rapid review of the evidence. Issue 3 (18th October 2016) - Coad, Jane; Toft, Alex; Lapwood, Susie; Manning, Joseph; Hunter, Mark; Jenkins, Huw; Sadlier, Clare; Hammonds, Julie; Kennedy, Ailsa; Murch, Simon; Widdas, David
Abstract : With the growing number of children and young people with complex care needs or life-limiting conditions, alternative routes for nutrition have been established (such as gastrostomy feeding). The conditions of children and young people who require such feeding are diverse but could relate to problems with swallowing (dysphagia), digestive disorders or neurological/muscular disorders. However, the use of a blended diet as an alternative to prescribed formula feeds for children fed via a gastrostomy is a contentious issue for clinicians and researchers. From a rapid review of the literature, we identify that current evidence falls into three categories: (1) those who feel that the use of a blended diet is unsafe and substandard; (2) those who see benefits of such a diet as an alternative in particular circumstances (eg, to reduce constipation) and (3) those who see merit in the blended diet but are cautious to proclaim potential benefits due to the lack of clinical research. There may be some benefits to using blended diets, although concerns around safety, nutrition and practical issues remain.